Analysis of complaints in the comments section on Air Selangor's Facebook page / Normah Ahmad ... [et al.] - Ahmad, Normah; Shaharuddin G, G. Sharina; Abdul Rashid, Nor Rasimah; Mohd Samsir, Sri Qamariah; Sharif, Sarinah (Universiti Teknologi MARA, 2022)
The speech act of complaints has often caught the attention of researchers in many perspectives. Most previous stud-ies on complaints relied on discourse completion task (DCT) data, and some used ethnographically obtained data. Nowadays, with the widespread use of the Internet, many human affairs have also shifted to online, including com-plaints. However, there is still not much research done on complaint speech act in an online setting. Therefore, this study has utilized the data of complaints in the comments section on the Facebook page of Syarikat Air Selangor. A to-tal of 74 complaints were obtained from 200 comments in the comments section on Air Selangor's Facebook page. Water consumers make complaints as a response to a notification of water supply disruptions in the Klang Valley. The data were analyzed using the framework introduced by Depraetere et al. (2020) and Decock & Depraetere (2018). The results showed that complainers preferred using only one and two components, namely the strategy of complaints and dissatisfaction or a combination of both. The results proved that the complainers employ more implicit complaint strategies and less explicit strategies. Although this study was conducted in an online setting, it was found that the complaints made were not too aggressive and did not use many harsh words. Most complaints only stop as far as component B, which is dissatisfaction, and do not escalate further. This study is significant because it can provide in-formation on how Malaysians utilise language, particularly when voicing complaints on social media.